Kekuatan Puntir dan Porositas Hasil Sambungan Las Gesek AlMg-Si dengan Variasi Chamfer dan Gaya Tekan Akhir - Tyagita, Dicky Adi; Irawan, Yudy Surya; Suprapto, Wahyono (Jurnal Rekayasa Mesin, 2014)
Friction welding is the most suitable method for joining aluminum alloys. Aluminum alloys have limitations heat to concentrate only in weld area when used arc or gas welding. That causes it is has good thermal conductivity. The parameters that influence on friction welding are friction time, compressive force, upset force, rotational speed, and chamfer angle. The purpose of the research was to know influence of chamfer angle and upset force on the Al-Mg-Si. The chamfer angles variated 0, 15°, 30°, 45° and upset force variated 157 kgf, 185 kgf and 202 kgf. Specimens were friction welded with rotation speed of 1600 rpm, compressive force 123 kgf for 120 seconds, and upset force variation by 157, 185, 202 kgf for 120 seconds. In addition torsion and porosity testing were also performed on friction welding product. Results showed that specimens with a chamfer angle 15 ° in various upset force has maximum shear strength, so were on specimens with a chamfer angle 15 ° has minimum percentage of porosity in various upset force.Keywords : shear strength, friction welding, chamfer angle, upset force, porosity and Al-Mg-Si